ANALISIS TENTANG PERSEPSI MAHASISWA UNIVERSITAS RIAU TERHADAP FUNGSI PARTAI POLITIK DI INDONESIA - Wiguna, Riyan; Erlinda, Sri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study was motivated by a political party functions that are the responsibility of political parties to run. Those functions such as; political communication, political socialization, political recruitment, political participation, articulation, aggregation and regulatory conflicts. So the authors take the title of the study